Efektifitas Ekstrak Daun Kesemek Hitam (Diospyros Nigra) Sebagai Alternatif Penurunan Kadar Glukosa Tikus Putih (Rattus Norvegicus) - Haryanto Haryanto; Suci Aulia Rahmadani; Rana Muthia Najwa; Afandi Afandi (Pusat Riset dan Inovasi Nasional, 2025)
Plants contain several active ingredients beneficial for health, one of which is the persimmon plant, known for its tannins and phenolic compounds. This research aims to determine the effect of Black Persimmon Leaf Extract (Diospyros nigra) as an alternative for lowering glucose levels in White Rats (Rattus norvegicus). This is a True Experimental research, which controls all external variables that could affect the experimental results. There are four control groups: a negative control using glucose and positive controls using extracts with concentrations of 15%, 30%, and 60%. The research data were measured using a UV-Vis Spectrophotometer and analyzed using One Way ANOVA with SPSS. The results of the Shapiro-Wilk normality test showed a significance value >0.05; Levene's Test for homogeneity showed a significance value >0.05; the One Way ANOVA test showed a significance value <0.05; and the Tukey HSD test showed a significance value >0.05. The objective of this research is to test the effectiveness of black persimmon leaves (Diospyros nigra) as an alternative to lowering blood glucose levels in white rats (Rattus norvegicus). Sample absorbance data were obtained using UV-VIS Spectrophotometry and analyzed using One Way ANOVA in SPSS.